Formation kinetics and mechanism of metastable vacancy-dioxygen complex in neutron irradiated Czochralski silicon. (July 2017) - Dong, Peng; Wang, Rong; Yu, Xuegong; Chen, Lin; Ma, Xiangyang; Yang, Deren
Abstract: We have quantitatively investigated the formation kinetics of metastable vacancy-dioxygen (VO2 ) complex in a structure of [VO + O i ], where a VO complex is trapped in a next-neighbor position to an interstitial oxygen atom (O i ). It is found that the VO annihilation is accompanied by the generation of metastable [VO + O i ] complex during annealing in the temperature range of 220–250 °C. The activation energy for [VO + O i ] generation appears at around 0.48 eV, which is much lower than the counterpart of stable VO2 complex. This indicates that the formation of [VO + O i ] complex originates from the reaction between VO and O i . The ab initio calculations show that the formation energy of [VO + O i ] complex is larger than that of VO2 complex, which means that [VO + O i ] complex is thermodynamically unfavorable as compared to VO2 complex. However, the binding energy of [VO + O i ] complex is positive, indicating that [VO + O i ] complex is stable against decomposition of VO and O i in silicon. It is believed that [VO + O i ] complex serves as the intermediate for VO to VO2 conversion. Graphical abstract: Highlights: The formation of metastable vacancy-dioxygen (VO2 ) complex in silicon, with a structure of [VO + Oi ] is quantitatively investigated, which has little been experimentally reported. Combined with the evolution of interstitial oxygen and VO complex during annealing, the mechanisms for [VO + Oi ] formation and VO annihilation have been discussed.